ҚАРАҚАЛПАҚ ТИЛИНДЕГИ СОМАТИКАЛЫҚ ФРАЗЕОЛОГИЗМЛЕРДИҢ МӘНИЛЕРИ ҲАҚҚЫНДА - Кеулимжаева, У.К. (ILIM hám JÁMIYET, 2021)
In the given article are proved the meanings of synonymous phraseological units using features with the component “ko’z (eye)” on the basis of the examples taken from literary works. In the literary works were investigated the use of synonymous phraseological units in forming the character, in giving the lingual characteristics to the character, the external portrait of the character, his world of internal life, his behavior, in describing his worldview.